“Diseño del sistema eléctrico de la planta procesadora de lácteos (MILMA LAC) ubicada en el Cantón Montufar Provincia del Carchi” - Espinoza Zamora, Juan Rodrigo (2021)
Franklin Hernán Vásquez Teneda This project research is focused on specific stages of the study and design plan, where part of the compilation of a theoretical basis leads to the study and analysis for a selection of the elements that make up the new medium and low voltage electrical system, each element of the network such as conductors, protections, power capacity, ground mesh among others. It will begin by calculating the total demand of the electrical load based on the electrical requirements of the industry, then an analysis of the new area will be carried out in which the different medium and low voltage circuits will be distributed, giving way to planning according to the plans Delivered by the owner of the plant, subsequently, the selection will proceed according to the technical characteristics of the elements such as conductors, thermo magnetic keys, distribution boards and other elements that fit with an acceptable budget for the project, based on the rules and regulations of the MEER the new electrical design will have the ability to support future loads that will allow the company to grow and guarantee its productivity, the new electrical system will also have a grounding system that will prevent overvoltages or current leakage from damaging the useful life of the equipment and machinery involved in the different production processes in addition to having a transformation chamber that will guarantee the supply of electrical energy to the different circuits, which will be in a position to support an increase in planned load in the future when carrying out this project, it is intended that the Milma Lac company count with an electrification system with the highest standards of safety and reliability.